A high-strength water-permeable and water-storage brick and its preparation method

By using modified water -absorbing resin ice grains and water -transmitting bricks pre -mixture to prepare high -intensity transparent merging water storage tiles, the problems of complex storage tile structure, low strength, and limited water storage capacity have been solved. Long -term water storage and good road adjustment effects.

CN117342842BActive Publication Date: 2025-01-28HUAXIN CEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311268645.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-01-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The existing water storage bricks have complex structures, low strength, limited water storage capacity, short water storage time, and difficult to effectively improve the road surface temperature and humidity.

Method used

The main raw materials are used to use modified water absorption resin ice particles and permeable bricks. After processing through the process of stirring, aging, freezing, crushing, and screening, a high -strength transparent merging tile is formed. Batch production.

Benefits of technology

The high -intensity and long -term water storage can be achieved, which can maximize the absorption of rainwater and reduce the problem of road area water. At the same time, it takes into account good water storage performance and long -term adjustment of the temperature and humidity of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004474912420000051
    Figure BDA0004474912420000051
Patent Text Reader

Abstract

The invention discloses a high-strength permeable and storage-type water-storage brick, which uses modified water-absorbing resin ice particles and permeable brick premix as main raw materials, wherein the modified water-absorbing resin ice particles are obtained by stirring, mixing, aging, freezing, crushing and screening a semi-saturated water-absorbing resin and a hydrophobic polymer emulsion. The invention introduces modified water-absorbing resin ice particles formed by a semi-saturated water-absorbing resin and a hydrophobic polymer emulsion into the permeable brick premix, which can effectively improve the dispersion performance of the water-absorbing resin in the mixture and effectively reduce the weak points of the skeleton strength. When the obtained water-storage brick meets water, it first permeates water and then stores water, which can take into account good permeability, long-term water storage and strength, etc.; and the structure involved is simple, the preparation method is relatively simple, the operation is convenient, and it is suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to a high-strength permeable and storage-type water-storage brick and a preparation method thereof. Background Art

[0002] With the continuous development of urbanization, a large number of concrete pedestrian pavements have been laid in cities. Rainwater in the rainy season is difficult to penetrate into the ground, which easily causes waterlogging on the road and other problems that affect pedestrian traffic; heat absorption in summer will greatly increase the road surface temperature, aggravating the urban heat island effect. From the current status of urban construction, the existing pavement with permeable function includes permeable pavement materials and pavement base, and the paving cost involved is relatively high. Laying low-cost pavement water storage bricks with large rainwater storage capacity has become an important way to achieve urban sponge construction.

[0003] At present, the main preparation method of water storage bricks is to design a water storage cavity in the brick body to meet the water storage effect, such as CN112853848A, CNCN217078265U, CN112523023A, etc., but there are also significant problems, such as: the brick body structure is complex, which is not conducive to mass production; the existence of the water storage cavity greatly reduces the strength of the brick body, and the brick body is easy to be damaged during the laying process or later use; the water storage capacity is limited by the size of the brick body and the size of the water storage cavity; the water storage time is short, and the water in the water storage cavity will quickly penetrate into the ground or evaporate into the air, making it difficult to achieve the purpose of improving the temperature and humidity of the road surface for a long time. Summary of the invention

[0004] The main purpose of the present invention is to provide a high-strength permeable and storage-type water storage brick, which has a simple structure, high strength, large rainwater absorption capacity, and long water storage time; and the preparation method involved is relatively simple, easy to operate, and suitable for popularization and application.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A high-strength permeable and storage-type water-storage brick uses modified water-absorbing resin ice particles and permeable brick premix as main raw materials, wherein the modified water-absorbing resin ice particles are obtained by stirring, mixing, aging, freezing, crushing and screening semi-saturated water-absorbing resin and hydrophobic polymer emulsion.

[0007] In the above scheme, the mass ratio of the modified water-absorbing resin ice particles to the permeable brick premix is ​​6 to 10:100.

[0008] In the above scheme, the semi-saturated water-absorbing resin is obtained by adding 8 to 12 parts of a highly water-absorbing resin into 100 to 200 parts of water, and stirring the mixture so that the water is completely absorbed by the water-absorbing resin.

[0009] Furthermore, the stirring treatment time is 10 to 20 minutes, and the stirring rate is 45 to 90 r / min.

[0010] In the above scheme, the mass ratio of the semi-saturated water-absorbing resin to the hydrophobic polymer emulsion is 8-12:1-2; preferably, the two are stirred and mixed for 10-15 minutes, and the stirring rate is 30-60r / min; after stirring, the aging is 2-6 hours, the aging temperature is 20-35°C, and the relative humidity is 50-80%.

[0011] In the above scheme, the freezing temperature is -10 to -20°C and the time is 1 to 2 hours.

[0012] In the above scheme, the water absorption rate of the super absorbent resin is not less than 500 times, the saturated water absorption expansion multiple is 200-1000 times, and the particle size is 0.02-0.05 mm. The specific composition of the super absorbent resin is not strictly limited, and can be selected from polymethacrylic acid resin, polymethacrylic acid-acrylamide resin, etc.

[0013] In the above scheme, the viscosity of the hydrophobic polymer emulsion is 50-200 mPa·s, the solid content is 3-6%, and the minimum film-forming temperature is 10-20°C; preferably, a diluted concrete water-based release agent is used, such as a silicone oil water-based release agent or a wax water-based release agent.

[0014] Furthermore, the viscosity of the concrete water-based release agent used is 100-300 mPa·s, and the solid content is 15-30%.

[0015] In the above scheme, the dilution step is to dilute with water 5 to 10 times and then stir evenly; wherein the stirring time is 20 to 60 minutes, and the stirring rate is 30 to 60 r / min.

[0016] In the above scheme, the components and their weight proportions in the permeable brick premix include: 73-79 parts of crushed stone, 15-25 parts of cement, 5-6 parts of water, and 0.1-0.4 parts of high-efficiency water reducer. Among them, the crushed stone particle size is 5-10 mm, the cement is preferably ordinary Portland cement of P·O42.5 and above, and the high-efficiency water reducer is preferably a polycarboxylate water reducer with a water reduction rate of 30-40%.

[0017] Furthermore, the temperature of the permeable brick premix should be controlled at 5-15°C; the temperature control method of the permeable brick premix is ​​not limited, such as using ice water to prepare the permeable brick premix, using water spray ventilation to reduce the temperature of crushed stone, etc.

[0018] In the above scheme, after crushing, the obtained ice particles are screened.

[0019] Furthermore, the screening step adopts a two-stage screening process, wherein the crushed frozen modified water-absorbing resin is first passed through a round hole sieve with a sieve hole size of 1.25 to 2.5 mm, and the sieve underflow is taken; and then passed through a strip sieve with a sieve hole length of 1.25 to 2.5 mm and a width of 0.3 to 0.5 mm, and the sieve overflow is taken to obtain the modified water-absorbing resin ice particles.

[0020] The preparation method of the high-strength permeable and water-storage combined brick comprises the following steps: weighing 6-10 parts of modified water-absorbing resin ice particles and 100 parts of permeable brick premix, stirring evenly and then vibrating to form a brick blank; and naturally curing for 7-14 days to obtain a finished brick.

[0021] In the above scheme, the stirring time is 2 to 3 minutes, and the stirring rate is 90 to 120 r / min.

[0022] In the above scheme, vibration molding is completed within 1 to 3 minutes after uniform stirring.

[0023] In the above scheme, the vibration frequency during vibration molding is 90 to 120 Hz, and the time is 6 to 10 seconds.

[0024] In the above scheme, the natural curing conditions are temperature 20-40°C and relative humidity 50-70%.

[0025] The performance optimization mechanism of the water storage bricks of the present invention includes:

[0026] 1) The main factors affecting the strength of water storage bricks are pore distribution and the strength of the cement-stone skeleton. The present invention introduces a highly absorbent resin as a water storage material (without strength). After mixing, aging, freezing, crushing, screening and other processes, modified highly absorbent resin ice particles with a smooth and hard surface and high sphericity are obtained. During molding, the highly absorbent resin ice particles are mainly filled in the pore structure of the water storage brick without overlapping with the cement-stone skeleton. At the same time, the weak points of the skeleton strength can be effectively reduced to ensure the strength of the water storage brick.

[0027] 2) Super absorbent resins tend to stick together and aggregate after absorbing water; in the present invention, super absorbent resins are frozen and crushed to form fine ice particles, which can be evenly distributed during the mixing process with the premix of permeable bricks, effectively avoiding the negative impact of resin agglomeration and other problems on strength and water storage properties.

[0028] 3) During the aging process, the semi-saturated resin absorbs the water in the diluted polymer emulsion to form a hydrophobic film, which can effectively reduce the adsorption of the water-absorbent resin on the cement slurry in the permeable brick premix during the stirring process. While effectively ensuring that the cement slurry is mainly wrapped on the surface of the stone particles to provide strength, it can effectively avoid the problem that the cement slurry is wrapped on the surface of the water-absorbent resin and affects the water storage effect; in addition, during the preparation of the frozen modified water-absorbent resin, the water inside the water-absorbent resin forms ice crystals, expands in volume, and tears the hydrophobic film formed on the surface of part of the resin. The water can enter the resin through the cracks to ensure the water storage performance.

[0029] 4) It has the function of water permeability and water storage. The polymer absorbed on the surface of the resin particles dries to form a film, which inhibits the contact between the resin particles and water. When the water storage bricks in a dry state meet water, the water first flows out from the pores of the water storage bricks. Since the particle size of the resin particles in a dry state is small, the water permeability coefficient is high in the initial stage. As the soaking time of the resin particles increases, the water gradually penetrates into the interior of the resin from the cracks of the hydrophobic film, and the volume of the resin particles expands after absorbing water, the cracks gradually expand, and the water absorption rate increases significantly, thereby showing excellent water storage performance.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1) When the water-storage bricks come into contact with water, they first penetrate water and then store water, which can absorb rainwater to the maximum extent and reduce the problem of water accumulation on the road. At the same time, they can also take into account good water storage performance, which is conducive to long-term regulation of road surface temperature and humidity;

[0032] 2) The water storage brick has a simple structure, and the super absorbent resin is mainly distributed in the pores of the skeleton. There is no need to design an additional water storage cavity, and its local damage will not affect the water storage performance; the super absorbent resin has a large water absorption expansion rate, and can completely fill the skeleton pores when saturated with water. Impurities such as mud and dust in rainwater are not easy to block, which can effectively ensure its water storage performance;

[0033] 3) The modified water-absorbing resin has good water retention; water enters the internal structure of the resin and forms hydrogen bonds with the hydrophilic groups, and the energy required for evaporation increases. In addition, the film formed by the drying of the polymer can also inhibit water evaporation, further enhancing the long-term regulating effect of the water storage brick on the temperature and humidity of the road surface. DETAILED DESCRIPTION

[0034] The present invention will be further described in detail below in conjunction with the embodiments to facilitate a clearer understanding of the present invention, but they do not limit the present invention.

[0035] In the following examples and comparative examples, the super absorbent resin is polymethacrylic acid resin, with an average particle size of 0.03 mm, a water absorption rate of 950 times, and a saturated water absorption expansion multiple of 400 times. A vinyl silicone oil emulsion (silicone oil water-based release agent) produced by Shandong Dayi Chemical Co., Ltd. is used, with a viscosity of 150 mPa·s, a solid content of 23%, and a minimum film-forming temperature of 14°C; after diluting it 5 times with water, the resulting hydrophobic polymer emulsion has a viscosity of 95 mPa·s, a solid content of 4.5%, and a minimum film-forming temperature of 15°C.

[0036] The raw materials of the permeable brick premix include: 75 parts of crushed stone, 20 parts of cement, 5 parts of water, and 0.3 parts of high-efficiency water reducing agent; wherein, the particle size of the crushed stone is 8-10 mm, the cement is P·O42.5 ordinary silica cement; the water reducing agent is polycarboxylic acid high-efficiency water reducing agent, and the water reduction rate is 35%.

[0037] Example 1

[0038] A high-strength water-permeable and water-storage-combined brick, the preparation method of which comprises the following steps:

[0039] 1) Take 10 parts of super absorbent resin and 150 parts of water, stir them at a rate of 60r / min for 15min to obtain a uniform semi-saturated absorbent resin;

[0040] 2) taking 10 parts of a semi-saturated resin and 1.5 parts of a diluted hydrophobic polymer emulsion (a vinyl silicone oil emulsion diluted 5 times with water and stirred evenly, the stirring time is 30 minutes, and the stirring rate is 30 r / min), stirring at a rate of 40 r / min for 15 minutes; aging for 5 hours after the stirring, the aging temperature is 25° C., and the relative humidity is 65%; and then freezing treatment (-15° C., 1 hour) is performed to obtain a frozen modified water-absorbing resin;

[0041] 3) crushing the obtained frozen modified water-absorbing resin, and then passing it through a round hole sieve and a strip sieve in turn to obtain modified water-absorbing resin ice particles that meet the particle size requirements and have a high sphericity; wherein the round hole sieve has a sieve hole size of 2.5 mm; the strip sieve has a sieve hole length of 2.5 mm and a sieve hole width of 0.5 mm;

[0042] 4) 8 parts of modified water-absorbing resin ice particles and 100 parts of permeable brick premix (temperature 12° C.) were mixed and vibrated to obtain a brick; wherein the mixing time was controlled at 2 min and the mixing rate was controlled at 120 r / min; the vibration molding was completed within 3 min after the mixing was uniform; the vibration frequency during the vibration molding was 90 Hz and the time was 8 s;

[0043] 5) The bricks are naturally cured for 14 days to obtain the high-strength permeable and water-storage combined bricks; the natural curing conditions are a temperature of 30° C. and a relative humidity of 55%.

[0044] Example 2

[0045] A high-strength permeable and storage-type water-storage brick, the preparation method of which is substantially the same as that of Example 1, except that 10 parts of frozen modified water-absorbing resin and 100 parts of permeable brick premix are taken.

[0046] Example 3

[0047] A high-strength water-permeable and water-storage brick, the preparation method of which is substantially the same as that of Example 1, except that 10 parts of a semi-saturated resin and 2 parts of a hydrophobic polymer emulsion are taken.

[0048] Comparative Example 1

[0049] A water storage brick, the preparation method of which is substantially the same as that of Example 1, except that the semi-saturated water-absorbing resin does not use a hydrophobic polymer emulsion.

[0050] Comparative Example 2

[0051] A water storage brick, the preparation method of which is substantially the same as that of Example 1, except that: a semi-saturated water-absorbing resin and a hydrophobic polymer emulsion are evenly stirred and then directly stirred with a permeable brick premix.

[0052] Comparative Example 3

[0053] A water storage brick, the preparation method of which is substantially the same as that of Example 1, except that the crushed modified water-absorbing resin ice particles are directly mixed with the permeable brick premix after passing through a 2.5 mm round hole sieve.

[0054] Comparative Example 4

[0055] A water storage brick, the preparation method of which is substantially the same as that of Example 1, except that the semi-saturated resin and the hydrophobic polymer emulsion are directly frozen after being stirred evenly.

[0056] Comparative Example 5

[0057] A water storage brick, the preparation method of which is substantially the same as that of Example 1, except that the semi-saturated water-absorbing resin is directly modified by using vinyl silicone oil emulsion (undiluted polymer emulsion).

[0058] The water storage bricks obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for mechanical properties, water permeability and water storage performance, and the results are shown in Table 1.

[0059] Table 1 Water storage brick performance test results

[0060]

[0061] Note: Initial water permeability refers to the water permeability measured after the water storage brick is cured and dried at 50℃ to constant weight. Water permeability after soaking for 1~2h refers to the water permeability measured after the water storage brick is cured and dried at 50℃ to constant weight and then soaked for 1~2h. Saturated water permeability refers to the water permeability measured when the water storage volume reaches saturation after the curing. Water retention time refers to the time required for the water storage brick to be dried at 40℃ to constant weight when it reaches saturated water storage volume.

[0062] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A high-strength water-permeable and water-storage brick, characterized in that: The method uses modified water-absorbing resin ice particles and permeable brick premix as main raw materials, wherein the modified water-absorbing resin ice particles are obtained by stirring, mixing, aging, freezing, crushing and screening semi-saturated water-absorbing resin and hydrophobic polymer emulsion; The mass ratio of the modified water-absorbing resin ice particles to the permeable brick premix is ​​6-10:100; The temperature of the permeable brick premix is ​​controlled at 5-15°C; The hydrophobic polymer emulsion has a viscosity of 50-200 mPa•s, a solid content of 3-6%, and a minimum film-forming temperature of 10-20°C; The specific steps of screening include: first passing the crushed frozen modified water-absorbing resin through a round hole sieve with a sieve hole size of 1.25-2.5 mm, and taking the sieve underflow; then passing the sieve through a strip sieve with a sieve hole length of 1.25-2.5 mm and a width of 0.3-0.5 mm, and taking the sieve overflow; The semi-saturated water-absorbing resin is obtained by adding 8 to 12 parts of a highly water-absorbing resin to 100 to 200 parts of water, and stirring the mixture so that the water is completely absorbed by the water-absorbing resin. The mass ratio of the semi-saturated water-absorbing resin to the hydrophobic polymer emulsion is 8-12:1-2.

2. The high-strength water-permeable and water-storage-combined brick according to claim 1 is characterized in that: The freezing temperature is -10 to -20°C and the freezing time is 1 to 2 hours.

3. The high-strength water-permeable and water-storage-combined brick according to claim 1 is characterized in that: The water absorption rate of the super absorbent resin is not less than 500 times, the saturated water absorption expansion multiple is 200-1000 times, and the particle size is 0.02-0.05 mm.

4. The high-strength water-permeable and water-storage-combined brick according to claim 1 is characterized in that: The components in the permeable brick premix and their weight proportions include: 73-79 parts of crushed stone, 15-25 parts of cement, 5-6 parts of water, and 0.1-0.4 parts of high-efficiency water reducing agent.

5. The method for preparing the high-strength water-permeable and water-storage-combined brick according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: weighing 6-10 parts of modified water-absorbing resin ice particles and 100 parts of permeable brick premix, stirring the mixture evenly, and then vibrating the mixture to obtain a brick blank; and naturally curing the mixture for 7-14 days to obtain a finished brick.

Citation Information

Patent Citations

  • High-strength drainage and water storage type municipal road floor tile

    CN112523023A

  • Easy-to-fire drainage and storage combined water storage brick

    CN112853848A

  • Water storage brick

    CN217078265U

  • Absorbing material and preparation method thereof

    CN108159478A

  • Water-permeable brick base layer production method and water-permeable brick

    CN110194619A